Transformaciones culturales y comunicativas de los pueblos Emberá Dóbida y Chamí del Alto Baudó - Restrepo Moreno, José Miguel; Silva Bolívar, Juliana; Vergara Vélez, John Fredy (Folios, revista de la Facultad de Comunicaciones y Filología, 2025)
This investigation presents a theoretical review intended to serve as the foundation for a feature film aimed at making visible the cultural and communicative transformations that have occurred as a result of the armed conflict in the ancestral Emberá Dóbida and Emberá Chamí communities, located in Alto Baudó, Chocó. The topic is approached through the concepts of culture, communication, and territory, as these three axes underpin tradition and its transformations brought about by changes in space. We examinehow displacement and uprooting experienced by members of these communities ‒mainly to urban centers such as Quibdó and Medellín‒ have generated deep conflicts, in which inhabitants are forced to detach from their culture. This leads to a sense of invisibility and non-belong-ing, as survival in urban settings is governed by dynamics in which ethnic identity is no longer a meaningful reference point.